Multimodality imaging of Xp11.2 translocation/TFE3 gene fusion associated with renal cell carcinoma: a case report - Huang, Wenpeng; Peng, Yushuo; Zhang, Yongbai; Qiu, Yongkang; Liu, Yi; Wang, Aixiang; Kang, Lei (Frontiers in Medicine, 2023)
Background: Xp11.2 translocation/TFE3 gene fusion associated with renal cell carcinoma (Xp11.2 RCC) exhibits unique biological characteristics and is associated with an increased incidence of tumor thrombosis, lymph node metastasis, and advanced disease stages. Multimodality imaging, including US, contrastenhanced CT, multi-parametric MRI, and 18 F-FDG PET/CT plays a crucial role in the preoperative diagnosis and differentiation of renal tumors.Case Report: A 15-year-old female presented with lumbar pain worsened, and developed persistent painless hematuria. To further clarify the staging, the patient underwent 18 F-FDG PET/CT. PET/CT images showed multiple irregular occupancies in the right kidney with unclear borders, showing a heterogeneous increase in 18 F-FDG uptake, with SUVmax values ranging from 2.3 to 5.2 in the routine imaging phase (60 minutes post-injection), compared to SUVmax values ranging from 2.8 to 6.9 in the delayed imaging phase (160 minutes post-injection). Additionally, multiple enlarged and fused lymph nodes were observed in the medial part of the right kidney and the retroperitoneum, exhibiting a heterogeneous increase in 18 F-FDG uptake, with SUVmax values ranging from 4.1 to 8.7 in the routine imaging phase, compared to SUVmax values ranging from 4.4 to 9.1 in the delayed imaging phase. The postoperative pathology, immunohistochemistry, and molecular analysis of histiocytes were consistent with a diagnosis of Xp11.2 RCC. One month after surgery, enhanced-CT examination of the patient revealed lung metastasis, peritoneal metastasis, and multiple lymph node metastases throughout the body, with an overall survival of 16 months.Xp11.2 RCC exhibits unique biological characteristics and is associated with an increased incidence of tumor thrombosis, lymph node metastasis, and advanced disease stages. Long-term follow-up is essential to monitor the likelihood of recurrence and metastasis. 18 F-FDG PET/CT examination can comprehensively visualize the lesion's location and extent, providing a basis for clinical tumor staging and aiding in treatment monitoring and follow-up. Further advancements in molecular imaging technologies and the development of novel tracers hold great promise in advancing the diagnosis and management of RCC, ultimately contributing to better patient outcomes and overall disease management.